2023
DOI: 10.4102/sajems.v26i1.4758
|View full text |Cite
|
Sign up to set email alerts
|

Micro-economic drivers of the South African foundry industry

Abstract: Background: The foundry industry plays an important economic role in South Africa and all efforts should be made to sustain the industry. However, the problem is that many foundries are closing down due to economic factors.Aim: The primary research objective was to identify from literature the micro-economic drivers applicable to the sustainable competitive advantage (SCA) of foundries in South Africa. The secondary objectives were to benchmark the perceptions of stakeholders in the most prominent micro-econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…An industry that can substantially contribute towards job creation is the foundry industry (Phiri, Tolmay & Van Schalkwyk 2023). The metal foundry industry in South Africa is key in the supply of castings used predominantly in the manufacturing sector which includes the mining and automotive industries and has been faced with several challenges which have either resulted in the downsizing and/or closure of foundry companies (Phiri et al 2023;Statistics South Africa 2023).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…An industry that can substantially contribute towards job creation is the foundry industry (Phiri, Tolmay & Van Schalkwyk 2023). The metal foundry industry in South Africa is key in the supply of castings used predominantly in the manufacturing sector which includes the mining and automotive industries and has been faced with several challenges which have either resulted in the downsizing and/or closure of foundry companies (Phiri et al 2023;Statistics South Africa 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Wang (2021:1) suggests that a better comprehension of SCA is crucial for firms that seek 'consistent growth'. Although factors internal to the firm (micro-economic factors) can influence competitiveness (Phiri et al 2023), research has also shown that the macroeconomic factors are also critical in 'facilitating or impeding the firm's ability to compete' (Siudek & Zawojska 2014:102-103). A strategic core concern for management should be understanding how a firm's macroeconomic conditions affect its long-term competitiveness (Phiri et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations